Особенности развития специальной выносливости юных дзюдоисток 15-16 лет - Дадабаев, О.Ж. (SCIENCE and SOCIETY, 2021)
The article describes the method of increasing the special endurance of female judokas 15-16 years old. Also, the dynamics of indicators of general and special physical fitness of female judokas has been analyzed.
Keywords: sports; young judokas; special endurance; physical fitness; technique